Aflatoxins Recent Advances and Future Prospects - Razzaghi-Abyaneh, Mehdi (IntechOpen, 2013)
This book is broadly divided into five sections and 17 chapters, highlighting recent advances in aflatoxin research from epidemiology to molecular genomics and control measures, biocontrol approaches, modern analytical techniques, economic concerns and underlying mechanisms of contamination processes. This book will update readers on several cutting-edge aspects of aflatoxins research with useful up-to-date information for mycologists, toxicologists, microbiologists, agriculture scientists, plant pathologists and pharmacologists, who may be interest to understanding of the impact, significance and recent advances within the field of of aflatoxins with a focus on control strategy.